To the Matter of Implementation of Radio Engineering Data Transmission System with APSK-N-signal based on the Theory of Resolution Time - Lerner, I. M.; Ilin, V. I.; Fayzullin, R. R.; Garifullina, G. A. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The paper is dedicated to solution the problem related to the practical implementation of a radio engineering data transmission system which is based on the theory of resolution time, in which amplitude-phase shift signals with N discrete signals are used. In this work, analytical expressions are obtained that allow taking into account the instability of the initial phase of the carrier of information signal when choosing a configuration of signal constellation. Block diagram for considered type ReDTS is presented. The selection data transmission algorithm is presented.